2006
DOI: 10.1097/01.hjr.0000214611.91490.5e
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, knowledge, and perception of heart disease among adolescents

Abstract: Our findings suggest that adolescents lack knowledge regarding the risk of cardiovascular disease and do not perceive themselves at risk for cardiovascular disease. These data will be useful in designing future preventive strategies and interventions aimed at this target population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 29 publications
(32 reference statements)
4
38
0
Order By: Relevance
“…An earlier study reported a higher level of knowledge among young respondents 36. Interestingly, a study in adolescents reported a very poor level of cardiovascular knowledge 54. Otherwise, knowledge levels rise linearly from childhood until middle age, when the level starts to plateau 55.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study reported a higher level of knowledge among young respondents 36. Interestingly, a study in adolescents reported a very poor level of cardiovascular knowledge 54. Otherwise, knowledge levels rise linearly from childhood until middle age, when the level starts to plateau 55.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerotic disease begins during childhood, yet only 16% of adolescents perceive CVD to be a risk to them in their lifetime [90]. Knowledge and education are crucial for every step of the Transtheoretical Model.…”
Section: Counseling Patients To Make Cardioprotective Lifestyle Changesmentioning
confidence: 99%
“…Vanhecke et al [7] described that atherosclerosis is the main precedent for cardiovascular disease and reported that intimal lesions appear in all the artery of heart and more frequently in right coronary arteries of children aged between 7-9 years.…”
Section: Etiology Of Cardiovascular Disease: Diet and Life Stylesmentioning
confidence: 99%